2010
DOI: 10.1007/s10714-010-1138-6
|View full text |Cite
|
Sign up to set email alerts
|

On Braneworld inflation models in light of WMAP7 data

Abstract: We are interested on studying various inflationary spectrum perturbation parameters in the context of the Randall-Sandrum type 2 Braneworld model. We consider in particular three types of potentials. We apply the slow-roll approximation in the high energy limit to constraint the parameter potentials by confronting our results to recent WMAP7 observations. We show that, for some values of the e-folding number N , the monomial potential provides the best fit results to observations data.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Note that in the limit A → 0, the scalar spectral index n s , the ratio r and dns d ln(k) coincides with Ref [39].…”
Section: Original Chaplygin Gassupporting
confidence: 83%
See 1 more Smart Citation
“…Note that in the limit A → 0, the scalar spectral index n s , the ratio r and dns d ln(k) coincides with Ref [39].…”
Section: Original Chaplygin Gassupporting
confidence: 83%
“…In the paper [38] the authors study the attractors solutions of the dynamical system of a scalar field endowed with monomial potentials, and shown that the behaviour found for monomial potentials is typical in realistic inflationary models. Furthermore, R.Zarrouki et all have studied various inflationary spectrum perturbation parameters with three types of potentials they shown that the monomial potential provides the best fit results to observations data [39]. This potential is given by…”
Section: Original Chaplygin Gasmentioning
confidence: 99%
“…Slow roll chaotic inflation in RSII braneworld cosmologies for a single field with a monomial potential V (φ) = V 0 φ p has been the subject of several investigations. Although early studies [39,40] found that the ratio of tensor-to-scalar modes was suppressed for inflation at high energy scales ρ σ, subsequent investigations [41][42][43][44][45] found instead an enhancement. Specifically, the spectral index, n s , and tensor-to-scalar ratio, r, in the RSII braneworld scenario are given respectively by where N is the number of e-folds.…”
Section: Jcap06(2014)018mentioning
confidence: 96%